Technoeconomic and thermodynamic aspects of the edge cutting machining optimization - Anatoliy A. Ryzhkin (Advanced Engineering Research, 2016)
The investigation objective is to develop a calculation method of selecting the optimum cutting speed corresponding to the minimum tool-wear rate. The analysis of the known optimization criteria such as tribological, thermal, energy and thermodynamic ones is made. The characteristics of their optimality through the cutting velocity (friction) are identified. Particular attention is paid to the experimental thermodynamic optimization criteria reflecting the fluctuating nature of friction and wear which are developed in Don State Technical University. It is shown that the maximum values of fluctuation criteria through varying the cutting speed characterize the increased dissipation capabilities of the cutting area. The formula for calculating the optimum cutting speed under the conditions of thermal balance on the lathe knife pads is determined. The formula contains cutting mode elements, tool geometry, contact loads and the deformation characteristic of the cutting process - chip velocity factor. The proposed analytical dependence allows selecting the optimum condition using calculations without costly wear resistant experiments.